Customer base Strategies (Global Journal of Management and Business Research, 2018)
Growing and sustaining the customer base of an organization is always a challenge to firms' especially in an industry that is highly competitive and where the cost of brand switching is relatively low. For an organization to adopt any strategy, the need to scan its environment will be necessary to avoid making a strategic blonder that is capable of causing an organization it's live as a corporate entity. The objective of the study is to identify and discuss strategies an organization can adopt in growing and sustaining its market share in a given industry. These strategies include; innovation strategy, market segmentation strategy, market expansion strategy, 80/20 business strategy, and customer relationship retention strategies. The study was supported by an empirical study on Customer Retention Practices on Firm Performance.